POWDER-MIXED ELECTRICAL DISCHARGE MACHINING OF BIOMEDICAL AND INDUSTRIAL GRADE ALLOYS - NANIMINA, ALEXIS MOUANGUE (2015)
The development of the mechanical industries and biomedical engineering nowadays requires alloy materials having good mechanical and physical properties. Shaping of parts made from "di ftlcult-to-cut" alloys is a challenge even when using non-conventional processes such electrical discharge machining. The limitations of existing processes in machining implants are surface modification, biocompatibility corrosion, residual stress and reducing of fatigue performance induced during the process. Powder-mixed electrical discharge machining (PMEDM) was hypothesized and employed to be a solution to address above mentioned problem. Yet this technique is still at its infancy stage and deserves more investigation. The objectives of this study is to desib'll and analyze PMEDM ··open" system, to analyze and synthesize PMEDM on biomedical grade titanium alloy and industrial grade molybdenum high speed steel (HSS), to generate PMEDM performance models for numeric output responses, and to test, analyze and synthesize effect of PMEDM on biomedical grade titanium alloy corrosion rate.